Cervical Lymphadenopathy in a Nonagenarian Woman: What to Think? - Chaves, Vanessa Meireles (Eur J Case Rep Intern Med, 2019)
Tuberculosis remains a worldwide public health problem. Cervical tuberculous lymphadenitis (TBL) or scrofula is the most common form of extrapulmonary tuberculosis, affecting the cervical lymph nodes. We report the case of a 93-year-old woman presenting with cervical adenopathies with 3 months duration. Fine needle aspiration (FNA) biopsy yielded a noncaseous granulomatous process, but was negative for Mycobacterium tuberculosis (MT). As the adenopathies had grown, an excisional biopsy was performed. An extensive study of infectious aetiologies was performed, including for MT, with a negative outcome. Owing to the persistence of cervical lymphadenitis with caseous granulomas, a diagnosis of TBL was strongly suspected and presumptive treatment was initiated. Afterwards, diagnostic confirmation was obtained by isolation of MT in the lymph node culture. The patient presented a favourable clinical outcome. This case highlights that a high index of suspicion is essential for the diagnosis of TBL, especially in the elderly, and emphasizes the importance of pursuing diagnostic confirmation, in which FNA and excisional biopsy plays a key role. LEARNING POINTS: The diagnosis of tuberculous lymphadenitis should be considered in all patients presenting with cervical adenopathies, especially in endemic areas, irrespective of the patient’s age. A high index of suspicion is essential for the diagnosis due to the wide range of conditions that can mimic the disease. Fine needle aspiration biopsy is appropriate as an initial diagnostic approach, with excisional biopsy recommended when the former is not diagnostic.